2009
DOI: 10.1523/jneurosci.0654-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Deafferentation of the Neocortex Using 192 IgG-Saporin Impairs Feature Binding In Rats

Abstract: The binding problem refers to the fundamental challenge of the CNS to integrate sensory information registered by distinct brain regions to form a unified neural representation of a stimulus. Although the human cognitive literature has established that attentional processes in frontoparietal cortices support feature binding, the neurochemical and specific downstream neuroanatomical contributions to feature binding remain unknown. Using systemic pharmacology in rats, it has been shown that the neuromodulator ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…Cortical cholinergic activity is critically involved in sensory perception and attention (9,13,23,24). Here we demonstrate that ACh signaling is an essential mechanism mediating the utilization of environmental stimuli to guide behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical cholinergic activity is critically involved in sensory perception and attention (9,13,23,24). Here we demonstrate that ACh signaling is an essential mechanism mediating the utilization of environmental stimuli to guide behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonizing the cholinergic muscarinic system resulted in disturbed initial feature binding in rats. (23–25) Visuospatial processing could be degraded in patients with DLB (and more so than in AD) by cholinergic deafferentation of visual association areas if such reductions in input result in the inability to either pull the salient features from the visual scene or to successfully reintegrate those features.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical cholinergic deafferentation did not affect the animals’ performance in blocks of unimodal trials in which all cues were either visual or auditory. In contrast, under the condition of modality uncertainty, the lesion caused a profound speed-accuracy trade-off, with correct responses requiring 700 ms longer in bimodal than in unimodal blocks of trials (for additional evidence illustrating disruption of basic attentional abilities by selective cholinergic lesions see, for example, Newman and McGaughy, 2008; Botly and De Rosa, 2009). The robustness and the selectivity of the cognitive impairments produced by such lesions is further supported, albeit indirectly, by a substantial number of experiments which concluded that removal of forebrain cholinergic neurons does not have strong effects on the performance of animals in tasks that do not explicitly tax attentional processes (Vuckovich et al , 2004; Frick et al , 2004).…”
Section: Acetylcholine and The Regulation Of Attentionmentioning
confidence: 99%